Zlata's diary : a child life in Sarajevo - Filipovic, Zlata (New York : Scholastic, 1994)
The Diary of thirteen year old girl living in Sarajevo, begun just before her eleventh birthday when there was still peace in her homeland.
Keywords: Filipovic, Zlata -- Diary; Diary -- Zlata Filipovic